Goosebumps: A Night in Terror Tower - Stine, R L (Scholastic Ltd, 1995)
Sue and her brother, Eddie, are visiting London when they run into a little problem. They can't find their tour group. Still, there's no reason to panic. No way their tour guide would just leave them. All alone. In a gloomy old prison tower. No way they'd get locked inside. After dark. With those eerie sounds. And a strange dark figure who wants them...dead.
Keywords: Horror & Ghost Stories; Juvenile Fiction